Amperometric determination of L-cysteine using a glassy carbon electrode modified with palladium nanoparticles grown on reduced graphene oxide in a Nafion matrix - Yusoff, Norazriena; Rameshkumar, Perumal; Mohamed Noor, An’amt; Huang, Nay Ming (Springer Verlag (Germany), 2018)
An amperometric sensor for L-Cys is described which consists of a glassy carbon electrode (GCE) that was modified with reduced graphene oxide placed in a Nafion film and decorated with palladium nanoparticles (PdNPs). The film was synthesized by a hydrothermal method. The PdNPs have an average diameter of about 10 nm and a spherical shape. The modified GCE gives a linear electro-oxidative response to L-Cys (typically at +0.6 V vs. SCE) within the 0.5 to 10 μM concentration range. Other figures of merit include a response time of less than 2 s, a 0.15 μM lower detection limit (at signal to noise ratio of 3), and an analytical sensitivity of 1.30 μA·μM−1·cm−2. The sensor displays selectivity over ascorbic acid, uric acid, dopamine, hydrogen peroxide, urea, and glucose. The modified GCE was applied to the determination of L-Cys in human urine samples and gave excellent recoveries.